Decision Usefulness Approach Of Accounting Information: Bagaimana Informasi Akuntansi Menjadi Useful ? - Puspitaningtyas, Zarah (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractApplication of decision usefulness approach to produce accounting information that is relevant and reliable. Relevant information, that has the capacity to affect the confidence of investors about future returns, and should be released in a timely manner.The concept of decision usefulness of accounting information plays an important role in identifying problems for users of financial reports and selection of accounting information that users of financial statements to make the best decision. To apply the concept of decision usefulness is necessary linkages with the various theories in economics and finance. Decision usefulness approach assumes that individual decision makers are rational, that is individuals who will choose the action that will yield the highest expected utility.